MULTIMODALITY THEORY AND DIGITAL SEMIOTICS: FOUNDATIONS OF LINGUISTIC ANALYSIS - Kamola Abdullayeva (International Journal of Literature and Language Studies, 2026)
Annotation: This article examines the theoretical and methodological potential of multimodality theory and digital semiotics in the study of contemporary Internet discourse. The aim of the research is to identify the mechanisms of meaning-making resulting from the interaction of verbal and non-verbal semiotic resources in digital communication. The study employs multimodal discourse analysis, social semiotic analysis, cognitive-linguistic analysis, and pragmatic analysis. The study further demonstrates that multimodal elements play a significant role in constructing virtual identities, expressing emotions, and enhancing communicative effectiveness. The results contribute to the development of multimodal discourse studies and provide a framework for investigating digital communication across different linguistic and cultural contexts.